Phytochemical constituent and antioxidant activity of extract from the leaves of Ocimum basilicum - ,R. Harisaranraj, K. Suresh, K. Sekar, S. Thangaraj, S. Saravana Babu (Journal of Phytology, 2010)
Ocimum basilicum leaf extracts of were investigated for phytochemical constituent and antioxidant activity. Tests for tannins, steroids, terpenoids, flavonoids and cardiac glycosides were positive in both ethanolic and aqueous extracts. The ethanolic extract of O. basilicum had a DPPH scavenging activity of 85.2% at 250Î¼g/ml and a reductive potential of 0.79 at 100 Î¼g/ml. These values were comparable with those of gallic acid, 91.1% at 250 Î¼g/ml and ascorbic acid, 0.76 at 60 Î¼g/ml as standards for DPPH scavenging activity and reductive potential, respectively. These findings suggest that the rich phytochemical content of O. basilicum and its good antioxidant activity may be responsible for its popular and wide traditional use.